Pembangunan Dan Modernisasi: Implikasinya Terhadap Tatanan Ekologi Dan Sosial - Aleksius Jemadu (Jurnal Administrasi Publik, 2003)
The paper starts from an idea that there is a fundamental difference between modernization and development. The former puts to much emphasis on industrialization with the effect that the social and ecological dimension of development is not adequately addressed. A genuine economic development should take into account social problems and ecological conservation. The incorporation of this social dimension into Indonesian economic development has been made more difficult after the economic crisis hit Indonesia in 1997. Therefore, an alternative model of economic development is needed so that the state and market might play their appropriate role in producing economic welfare for the people.